2014
DOI: 10.1039/c4tb01029a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a novel biomaterial with enhanced mechanical and conducting properties

Abstract: 5Conducting polymers combine the advantages of metal conductivity with ease in processing and biocompatibility; making them extremely versatile for biosensor and tissue engineering applications. However, the inherent brittle property of conducting polymers limits their direct use in such applications which generally warrant soft and flexible material responses. Addition of fillers increases the material compliance, but is achieved at the cost of reduced electrical conductivity. To retain suitable conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…[ 51 ] As examples of the utility of MOFs toward TENG technology, a family of zeolitic imidazole frameworks, HKUST‐1, etc., have elegantly been highlighted. [ 52–54 ] From the literature analysis, it can be understood that depending on the functional group, MOFs displayed positive or negative triboelectric effects. For instance, fluorine‐functionalized MOFs exhibited a high tribonegative nature due to the enhanced charge transport capability.…”
Section: General Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 51 ] As examples of the utility of MOFs toward TENG technology, a family of zeolitic imidazole frameworks, HKUST‐1, etc., have elegantly been highlighted. [ 52–54 ] From the literature analysis, it can be understood that depending on the functional group, MOFs displayed positive or negative triboelectric effects. For instance, fluorine‐functionalized MOFs exhibited a high tribonegative nature due to the enhanced charge transport capability.…”
Section: General Backgroundmentioning
confidence: 99%
“…Multiple works have reported the application of MOF in high‐performance TENG. [ 53,56,195–198 ] For instance, Khandelwal et al. first reported the use of zeolitic imidazole framework (ZIF) MOF‐based TENG for self‐powering systems and sensor applications ( Figure a).…”
Section: Progress In the Mof Applicationsmentioning
confidence: 99%
“…By coupling thiophene heterocycles with hydrolytically sensitive azomethine linkers, it is possible to create a conducting co-polymer containing an on-demand, degradable constituent that maintains the conjugated structure and does not compromise the material's bulk conductivity. Thiophene oligomers are convenient building blocks for the preparation of functional electroactive polymers and materials derived from thiophene have shown good in vitro compatibility [23,24,25,26]. Our synthetic strategy included the use of rapid microwave assisted synthesis (MWS), as previous studies have found the EAPs products of microwave assisted synthesis have greater molecular weight and conductivity values [27,28].…”
Section: Introductionmentioning
confidence: 99%